Determinants of Consumers' Intention to Use QR Code-Based Intelligent Packaging on Food Products: Evidence from the Indonesian Market - Rolando Gultom; Adi Zakaria Afiff (Sekolah Tinggi Manajemen IPMI, 2025)
This study examines the factors influencing consumers’ intention to use intelligent packaging based on QR Code technology for product authenticity verification in the Indonesian food sector, using the Value-based Adoption Model (VAM). The proposed model integrates seven core constructs: perceived usefulness, perceived enjoyment, perceived informativeness, perceived technicality, perceived fee, perceived privacy risk, and perceived value as a key mediating variable influencing intention to use. Data were collected from 263 respondents through an online questionnaire, with 249 valid responses analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The study supports five out of seven hypotheses, with perceived informativeness having the strongest indirect effect on adoption intention through perceived value. Perceived technicality and usefulness also positively influenced value, while perceived enjoyment and privacy risk were not supported by the data. A slight price increase negatively affected perceived value. Overall, perceived value mediated the relationship between technology benefits, costs, and adoption intention. The study extends the VAM framework in intelligent packaging and suggests directions for future research.